Juvenile dermatomyositis in a 4‐year‐old Kenyan girl. Issue 2 (17th January 2017) - Grijsen, Marlous L.; Mchaile, Deborah; Geut, Inge; Olomi, Raimos; Nwako, Maitseo; Requena, Luis; Howlett, William P.; Mavura, Daudi R.; Dekker, Marieke C. J.
Key Clinical Message: To our knowledge, this is the first case report of juvenile dermatomyositis (JDM) in Tanzania. It demonstrates that the characteristic cutaneous findings of JDM may easily be overlooked, especially on dark skin, and the difficulty of clinical management in resource‐constrained settings. Abstract : To our knowledge, this is the first case report of juvenile dermatomyositis (JDM) in Tanzania. It demonstrates that the characteristic cutaneous findings of JDM may easily be overlooked, especially on dark skin, and the difficulty of clinical management in resource‐constrained settings.